2022
DOI: 10.1177/23337214211053121
|View full text |Cite
|
Sign up to set email alerts
|

Depression: Determinants That Influence the Mental Health of Older People (60 Years +) in Botswana

Abstract: Correlates of depression in older people were explored in this study. The prevalence of depression was also calculated. Data were collected using a cross-sectional study stratified by district in urban and rural Botswana using the Patient Health Questionnaire. A snowballing technique was utilized to recruit older participants ( N = 378; age = 71.8; SD = 9.1) with low to high incomes. Univariate and multivariate analyses were used to investigate the associations among demographics, individual, social, and envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The quality of life of the elderly especially their psychological health would be affected through the personal and social changes they face at the beginning and in the course of the aging period. 1,33 Meanwhile, depression is one of the most important consequences of CVD, which can increase mortality by up to 20% in these patients. 18 In this study, 53.8% of the elderly suffered from varying levels of depression, and the mean depression score in the elderly felt into the mild category.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality of life of the elderly especially their psychological health would be affected through the personal and social changes they face at the beginning and in the course of the aging period. 1,33 Meanwhile, depression is one of the most important consequences of CVD, which can increase mortality by up to 20% in these patients. 18 In this study, 53.8% of the elderly suffered from varying levels of depression, and the mean depression score in the elderly felt into the mild category.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study indicated that depression can lower the medication adherence in the elderlies suffering from CVD by up to 26%. The quality of life of the elderly especially their psychological health would be affected through the personal and social changes they face at the beginning and in the course of the aging period 1,33 . Meanwhile, depression is one of the most important consequences of CVD, which can increase mortality by up to 20% in these patients 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another systematic review, this time investigating depression in people 50 years old and over, the authors identified five risk factors, in brief: bereavement, sleep disturbances, disabilities, history of previous depression, and female gender 7 . Twenty years on from this review, it appears that variables such as quality of life and loneliness may play an important role in the development of depression in older adults 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…7 Twenty years on from this review, it appears that variables such as quality of life and loneliness may play an important role in the development of depression in older adults. 8,9 Regarding what is known about the incidence, in a systematic review, after the inclusion of 20 articles in which adults were 70 years old or more, the authors observed a variation in the incidence values according to the classification of the depressive spectrum. Thus, for 'major depression', the incidence ranged from 1.7% to 7.6%, while for 'depressive symptoms', the upper limit of total incidence ranged from 19% to 22%.…”
Section: Introductionmentioning
confidence: 99%